2003
DOI: 10.1161/01.hyp.0000056108.73219.0a
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Intercellular Adhesion Molecule-1 in Hypertensive Cardiac Remodeling

Abstract: Abstract-Recently, we have shown that in rats with a suprarenal abdominal aortic constriction (AC), pressure overload induces early perivascular fibro-inflammatory changes (transforming growth factor [TGF]-␤ induction and fibroblast proliferation) within the first week after AC and then causes the development of cardiac remodeling (myocyte hypertrophy and reactive myocardial fibrosis) associated with diastolic dysfunction. Intercellular adhesion molecule (ICAM)-1 is implicated in the recruitment of leukocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 21 publications
6
67
0
Order By: Relevance
“…9,10 AC-induced inflammatory changes result in myocardial fibrosis in the early phase and diastolic dysfunction in the later phase. 9,11,12,19 In this study, AC induced cardiac remodeling and diastolic dysfunction associated with inflammatory changes and superoxide generation in control female rats. A growing body of evidence implicates vascular inflammation in cardiovascular diseases in postmenopausal hypertensive women.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…9,10 AC-induced inflammatory changes result in myocardial fibrosis in the early phase and diastolic dysfunction in the later phase. 9,11,12,19 In this study, AC induced cardiac remodeling and diastolic dysfunction associated with inflammatory changes and superoxide generation in control female rats. A growing body of evidence implicates vascular inflammation in cardiovascular diseases in postmenopausal hypertensive women.…”
Section: Discussionmentioning
confidence: 72%
“…13 A causal relationship between inflammation and reactive myocardial fibrosis and diastolic dysfunction has been established in AC rats: a neutralizing antibody against MCP-1 or intercellular adhesion molecule-1 not only abolished macrophage infiltration but also inhibited fibroblast proliferation, TGF-b upregulation and myocardial fibrosis in AC rats. 9,12 Anti-MCP-1 neutralizing antibody prevented the progression of diastolic dysfunction in AC rats. 9 The augmentation of cardiac inflammation induced by estrogen deficiency is implicated in the aggravation of myocardial fibrosis and diastolic dysfunction in OVX+AC rats.…”
Section: E2 Deficiency and Diastolic Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] In addition, we have shown that a subdepressor dose of candesartan not only prevents MCP-1 induction and macrophage infiltration but also ameliorates reactive myocardial fibrosis in pressure-overloaded hearts. 21 These findings suggest that the cardiac angiotensin II (angII) system triggers the fibroinflammatory process, independent of its pressor effect.…”
mentioning
confidence: 84%
“…Also, macrophages accumulated in the area adjacent to the arteries showing ICAM-1 expression. 6 The involvement of mast cells in the development of fibrosis in rats with postmyocarditis-dilated cardiomyopathy has been investigated and a significant correlation between myocardial fibrosis and cardiac mast cell density was obtained. The findings confirm the active participation of mast cells in the progression of myocardial fibrosis in rats with postmyocarditis-dilated cardiomyopathy.…”
Section: Inflammatory Markers Associated With Lvh and Diastolic Dysfumentioning
confidence: 99%